Introgression of submergence tolerance QTL (SUB1) into mega rice variety ADT (R) 46 through marker assisted back crossing (MABC) approach - Saminadane, Thirumeni; Jothiganapathy, Karthick; Krishnaswamy, Paramasivam; Subbarayan, Nadaradjan; Adhimoolam, Premkumar; Rai, Vandna; Bisht, Deepak Singh; Singh, Nagendra Kumar; Singh, Rakesh Kumar; Singh, Uma Shankar; Ismail, Abdelbagi (Springer, 2025)
Submergence is a major stress affecting crop yields in low-lying areas during the North-East monsoon from October to December in the Cauvery Delta Zone of Tamil Nadu. Heavy rainfall leads to short-term submergence impacting 2 to 3 lakh hectares annually in the Cauvery Delta Zone of Tamil Nadu and Puducherry. The SUB1 QTL responsible for 70% of phenotypic variation in submergence tolerance has been mapped to chromosome 9 in the tolerant landrace FR 13 A. Marker-assisted backcrossing was successfully employed in the transfer of SUB1 into many mega rice varieties such as Swarna and CR 1009, IR 64 etc., ADT (R) 46 is a popular high-yielding rice variety grown in Tamil Nadu and Puducherry during the Rabi(Samba) season but is susceptible to submergence during North East monsoon. To impart submergence tolerance in ADT (R) 46, Swarna sub1 was crossed to it to introgress SUB1 QTL through Marker Assisted Back Crossing strategy. In BC3F3 generation, 20 promising Near Isogenic Lines (NILs) were identified based on phenotypic screening under submerged condition and subsequently subjected to 50 K SNP chip analysis for estimating background genome recovery which revealed 89 to 96% recovery of the recurrent parent genome, ADT (R) 46. Based on the performance of 20 NILs for grain yield under flooded condition in submergence tanks and high genome recovery, three NILs—KR 16,022, KR 16,023, and KR 16,024 were nominated for multi-location testing through All India Coordinated Rice Improvement Project. Among them, IET 28,791 (KR 16024) recorded average grain yield of 3633 kg/ha under flooded condition when compared to ADT (R) 46 which yielded 1989 kg/ha only, showing yield advantage of over 82.75%. Under non-flooded contion it recorded grain yield of 6850 kg/ha which is statistically on par with ADT 46 (6796 kg/ha). While retaining all the desirable agronomic features of ADT (R) 46, IET 28,791 posses submergence tolerance. This improved submergent tolerant version of ADT 46 developed through marker-assisted backcrossing has the potential to significantly enhance farmer incomes in submergence-prone areas.